S Manajemen Kepala Ma’hadul Qur’an Dalam Mengoptimalisasi Program Tahfidz Qur’an di Sukorejo Situbondo Jawa Timur - Siti Nur Hajiyah; Hasyim Asy’ari (Saintifika Islamica, 2023)
This research is based on the fact that the implementation is so busy that the students really have to be able to manage their time both in carrying out their tahfidz and in their diniyyah schools. This researcher aims to analyze the management of Ma'hadul Qur'an heads in optimizing the Tahfidz Program in Sukorejo Situbondo, East Java, especially in its implementation. This management includes planning, implementation and evaluation systems used. This research uses qualitative research with a case study approach. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data collection, data reduction, data presentation, drawing conclusions, Triangulation used to test the validity of the data is Triangulation of techniques and sources. The results of this research show that the Management of the Head of Ma'hadul Qur'an in Optimizing the Tahfidz Program carried out several stages, namely starting from planning, the Head of Ma'hadul Qur'an carried out determining the objectives of the Ma'hadul Qur'an program by adjusting the vision and mission of the institution. Meanwhile, in its implementation, it forms a learning strategy that is in accordance with the tahfidz program which is to build students' awareness of time discipline. The final stage is to carry out evaluations which are carried out periodically, this evaluation is carried out twice a year, namely monthly evaluations and qubro evaluations